1994
DOI: 10.1111/j.1365-2141.1994.tb04877.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the coagulation cascade in severe falciparum malaria through the intrinsic pathway

Abstract: The mechanisms involved in the activation of the coagulation cascade in severe falciparum malaria were studied in 22 adult patients (19 male, three female) aged 18-45 (mean +/- SD 31 +/- 11) years. Of these, nine had multiple vital organ dysfunction, and bleeding occurred in four patients, two of whom died. During acute illness the reduction in plasma antithrombin III (AT III) concentrations and elevation in thrombin-AT III complexes were associated with significant reductions in factor XII and prekallikrein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
100
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 23 publications
5
100
0
Order By: Relevance
“…22 In a study of severe falciparum malaria cases by Clemenset R al PT was prolonged in 22.7% of the cases this was similar to the observations in our study. 10 In our study APTT was found to be increased in 12% of the patients.It was increased in 10% of the cases with falciparum malaria and 13.3% of cases with vivax malaria and 20% with mixed infection. In a study conducted by Roy S et al APTT was increased in 16.6% of the patients this was similar to what we observed in our study.…”
Section: Thrombocytopeniamentioning
confidence: 74%
See 1 more Smart Citation
“…22 In a study of severe falciparum malaria cases by Clemenset R al PT was prolonged in 22.7% of the cases this was similar to the observations in our study. 10 In our study APTT was found to be increased in 12% of the patients.It was increased in 10% of the cases with falciparum malaria and 13.3% of cases with vivax malaria and 20% with mixed infection. In a study conducted by Roy S et al APTT was increased in 16.6% of the patients this was similar to what we observed in our study.…”
Section: Thrombocytopeniamentioning
confidence: 74%
“…11 Coagulation cascade is activated via intrinsic pathway. 10 In severe infection PT and PTT may be prolonged and in few patients (<5%) bleeding may be significant. Intravascular thrombus formation is observed rarely at autopsy in fatal cases.…”
mentioning
confidence: 99%
“…IRBC adhesion may also affect permeability indirectly by inducing tissue factor production on endothelial cells and subsequent activation of the coagulation cascade, 65 as evidenced by elevated levels of circulating thrombin-antithrombin III complex, 66,67 the presence of activated thrombin 68 and fibrin deposition 69 on brain microvascular endothelium in postmortem brain tissues. Thrombin is known to induce permeability through PAR-1 which heterodimerizes with PAR-3 leading to G a13 -dependent calcium signaling, actin stress fiber formation and transient increases in endothelial permeability.…”
Section: Cytoadherencementioning
confidence: 99%
“…hemozoin, glycosylphosphatidylinositol anchor, and oxidized heme) are potentially proinflammatory and may participate in disease pathogenesis 43 -45. Microparticle production 21 which reportedly display TF and PS 46, and host responses such as activation of the contact pathway, complement system, and neutrophils-known to produce radical oxygen species (ROS) and to release procoagulant elastase (reviewed in ref 20)-may also play an important pro-inflammatory role in P. falciparum infection 15,18,19 . Finally, the plasma or local levels of anticoagulants (e.g.…”
Section: The Tissue Factor Model For Malaria Pathogenesismentioning
confidence: 99%
“…The main argument that supports this notion is the fact that the vast majority, perhaps all patients with mild and severe malaria, present elevated levels of D-dimers20, a specific marker of plasmin-mediated fibrin proteolysis in vivo 23 . Finally, it has been reported that hemostatic alterations correlate with parasitemia, thrombocytopenia, and/or severity of P. falciparum infection in a number of studies; in addition, antiparasitic treatment halts the coagulation disorder and improves clinical outcome [12][13][14][15][16][17][18][19][20] .Therefore, it is plausible that hemostatic alterations play a role in the disease progression and organ failure observed in malaria 16,20 .More recently, it has been demonstrated that P. falciparum-parasitized RBC (pRBC) induce tissue factor (TF) expression in the microvascular EC in vitro, and support the assembly of multimolecular coagulation complexes 10 . TF is the clotting initiator 24-26 and a structural member of the cytokine receptor family, which signifies the expansion of the adaptive immune system in vertebrates, indicating a close connection of the coagulation pathways with the host response to infection 27 .…”
mentioning
confidence: 99%